The Potent of Carrier Oil on Pretreatment of Crude Jatropha Curcas Oil - Dini Kurniawati; Iis Siti Aisyah (JEMMME (Journal of Energy, Mechanical, Material, and Manufacturing Engineering), 2020)
Jatropha curcas oil is a seed oil or bio-oil, which has advantages compared to others plant’s seed-oil.  The advantage of this oil is due to the fact that Jatropha oil does not compete with the food sector. In this research, the potential carrier oil testing was conducted to seek a way in improving the performance of Jatropha oil as lubricant oil, coolant or biodiesel. For this purpose, Jatropha oil was mixed with the other carrier oils in the variation of 0 – 45 %. Each variation was tested to obtain kinematic viscosity and density values. The results of this research was the carrier oils has the potential to be used as the mixing material since it can improve the physical properties of Jatropha oil, before the next process. Kinematic viscosity and density of Jatropha oil decreases as more percentage of mixed carrier oil was added.